Biocompatibility studies of natural rubber latex from different tree clones and collection methods - Floriano, Juliana Ferreira [UNESP]; Lima Silveira da Mota, Ligia Souza [UNESP]; Furtado, Edson Luiz [UNESP]; Vieira Rossetto, Victor Jose [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP] (Springer, 2014)
Natural rubber latex (NRL) has several features that make it an excellent biomaterial to promote the growth and repair of tissues, skin and bones. Most of the research with NRL membranes uses a mixture of different clones and chemical preservatives in the collection process. In this study, we compared five clones that produce NRL, seeking to identify their differences in biocompatibility. The clones studied were RRIM 600, PB 235, GT1, PR 255 and IAN 873 commonly found in plantations in Brazil. We did also study the effect of ammonia used during latex collection. NRL membranes were prepared aseptically and sterilized. In the in vitro tests, the membranes remained in direct contact with mouse fibroblasts cells for three periods, 24, 48 and 72 h. In the in vivo tests, the membranes were implanted subcutaneously in rabbits. The results indicated the biocompatibility of the membranes obtained from all clones. Membranes from the clones RRIM 600 and IAN 873 induced greater cell proliferation, suggesting greater bioactivity. It was found that the membranes made from latex that was in contact with ammonia during collection, showed cytotoxic and genotoxic effects in cultures, as well as necrosis, and increased inflammatory cells in the rabbit's tissues close to the implant.